Former à l'arbitrage pour maintenir les élèves au travail en éducation physique. Étude de cas en boxe française dans un collège de l'éducation prioritaire. - Teddy Mayeko
Sometimes criticized for their violence, combat sports have been taught in Physical Education and Sports for several years. Paradoxically, the combat sports are appreciated by the students, who practice French boxing in the form of an assault. Therefore, from an approach in didactic enriched by the theoretical and methodological foundations of the clinical activity we seek to understand how a Physical Education teacher teaching the French boxing to secondary school students in priority education zone can keep students engaged in work. The first results show that refereeing training, mainly based on four factors, has a significant influence on the class climate. This work seems moreover essential to the implementation of this sport in a context of viable learning and carrying educational values.